Continuous fast pyrolysis synthesis of TiO2/C nanohybrid lithium‐ion battery anode. Issue 9 (1st March 2021) - Wang, Xiaoyan; Funke, Axel; Cheng, Ya‐Jun; Song, Fang; Yin, Shanshan; Liang, Suzhe; Zuo, Xiuxia; Gao, Jie; Müller‐Buschbaum, Peter; Xia, Yonggao
Abstract: Continuous fast pyrolysis is developed for in situ synthesis of ultra‐small metal oxide nanoparticles embedded into three‐dimensional macroporous carbon matrix as demonstrated by the TiO2 /carbon nanohybrid. The TiO2 nanoparticles with the average size of 4.6 nm ± 0.6 nm are uniformly distributed in the in situ generated macroporous carbon matrix. When evaluated as an anode in a lithium‐ion battery, the macroporous TiO2 /C nanohybrid exhibits a reversible capacity of 483 mAh g –1 after 500 cycles at a current density of 67 mA g –1, which is 3.6 times higher than that of the TiO2 /C calcined in a conventional batchwise way. Besides, the capacity retains 93 mAh g –1 at a high current density of 670 mA g –1 . It reveals that the continuous fast pyrolysis is an efficient method to fabricate carbon composition based metal oxides as lithium‐ion battery anode materials. Abstract : Continuous fast pyrolysis is utilized synthesize carbon composition based metal oxides demonstrated by TiO2 /Carbon nanohybrid lithium‐ion battery anode, where better electrochemical performance in terms of reversible capacities and rate capabilities are exhibited compared to the product synthesized with the conventional batchwise calcination method due to presence of ultra‐small TiO2 nanoparticles and macroporous carbon matrix.